Transformational Leadership in Education: Harmonising Accountability, Innovation and Global Citizenship - Adeoye, Moses Adeleke; Baharun, Hasan; Munawwaroh, Izzatul (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This article explores integrating transformational leadership in educational settings, focusing on balancing accountability with innovation while fostering sustainability and global citizenship. The primary objective is to develop a theoretical framework that illustrates how academic leaders can effectively align these elements to enhance student outcomes and community engagement. A qualitative research design was employed, incorporating a literature review and case studies of five exemplary schools. The findings revealed that successful transformational leadership involves redefining accountability, promoting innovative teaching practices and embedding global citizenship into the curriculum. Key challenges include resistance to change, balancing assessment pressures and ensuring adequate professional development. However, schools implementing these strategies report can improve student engagement, academic performance, and community involvement. In conclusion, transformational leadership is essential for navigating the complexities of modern education. It empowers schools to thrive amidst accountability demands while fostering innovation and global awareness. The article recommends that educational leaders prioritise flexible assessment methods, invest in continuous professional development, and build strong community partnerships to sustain these initiatives. By adopting this comprehensive approach, schools can better prepare students to become responsible and engaged citizens in an increasingly interconnected world.